In Silico Study of Ethylene Biosynthesis: Seeking New Effectors of ACC Synthase and ACC Oxidase - Ayadi, Nada; Aloui, Sarra; Shaiek, Rabeb; Rokbani, Oussama; Raboud, Faten; Fattouch, Sami (Current Bioinformatics, 2016)
The phytohormone ethylene plays essential physiological roles throughout the life cycle of plants, mainly via promoting ripening and senescence of fruits and flowers. Accompanying the sharp climacteric increase in ethylene production, there is a surge of 1-aminocyclopropane-1-carboxylate (ACC) synthase (ACS) and ACC oxidase (ACO) activities. ACS converts S-adenosyl-L-methionine (SAM) to ACC, whereas ACO converts ACC to ethylene. Pretreating fruits or plants with specific ethylene-biosynthesis inhibitors can reduce the ripening and senescence for agronomic and commercial motives. In the present study, the in silico molecular docking method was used to predict the interaction of available 3D structures of both ACS (Malus domestica and Solanum lycopersicum) and ACO (Petunia hybrida) with a range of potential inhibitors. Obtained data revealed that the (2E,3E)-4-(2-aminoethoxy)-2-[(3-hydroxy-2-methyl-5[(phosphonooxy)methyl]pyridin-4- ylmethyl) imino] but-3-enoic acid (PPG) presents the best inhibitory effect on ACS (energy score, ΔG = -202.52 Kcal/mol), more than that of other widely reported vinylglycine and SAM analogues (ΔG > -118.22 kcal/mol). The present findings showed that 2-[(3-hydroxy-2-methyl-5-phosphonooxymethyl-pyridin-4-ylmethyl)-imino]-5-phosphonopent- 3-enoic acid (HEN), a PPG analogue exhibits a strong binding capacity (ΔG = -217.41 Kcal/mol) to the ACS supporting its potential use as a new effector to delay fruit ripening. The 2-amino-7-(4-methylphenyl)-7,8-dihydro-5(6H)- quinazolinone could be the more appropriate uncompetitive inhibitor of ACS (ΔG = -87.65 Kcal/mol). The 2-(9H-fluoren- 9-ylmethoxycarbonylamino)-2-methylpropanoic acid, a 2-aminoisobutyric acid analogue, has been found as a new preservative for plant (ΔG = -109.71 kcal/mol). The discovery of such chemical compounds will be helpful in ethylenebiosynthesis research and can offer potentially useful agrochemicals for quality improvement in post-harvest agricultural products that will benefit both local and export markets.
Keywords: molecular docking